2020
DOI: 10.1080/09720502.2020.1833459
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control strategies of non-pharmaceutical and pharmaceutical interventions for COVID-19 control

Abstract: In recent, non-pharmaceutical intervention (lockdown, quarantine, expended testing) and the pharmaceutical intervention (use of commonly used drugs) are the only available strategies to control the COVID-19 disease. Though the scientist all over the world are engaging themselves to find the way out the vaccine of COVID-19, still it is persisted unanswered how to oust the pandemic epidemic from the world. Generally, social distancing, using the mask, etc. are the only available policy to control the pandemic. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Compared with the statistical model, the deterministic model is more straightforward to investigate the spread of diseases and to understand how restrictive measures could control the epidemics. SEIR 7 , 8 , 10 , 11 models are widely adopted to predict the outbreak of COVID‐19, where the exposed component as the source of infection accounts for a large proportion of the spread of COVID‐19 and cannot be neglected. 12 Model parameters are usually obtained by fitting the infection data by Bayesian method and Markov chain Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the statistical model, the deterministic model is more straightforward to investigate the spread of diseases and to understand how restrictive measures could control the epidemics. SEIR 7 , 8 , 10 , 11 models are widely adopted to predict the outbreak of COVID‐19, where the exposed component as the source of infection accounts for a large proportion of the spread of COVID‐19 and cannot be neglected. 12 Model parameters are usually obtained by fitting the infection data by Bayesian method and Markov chain Monte Carlo method.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic system ( 11 ) is containing two infected classes and V . Following the approach of [ 14 ], the two matrices required in computation of basic reproduction number are and at , and they are defined as follows: Thus, we get the next-generation matrix of the system ( 11 ) as Let us consider be the eigenvalues of the matrix and the spectral radius of the matrix is defined as . The basic reproduction number ( ) of the system ( 11 ) is the spectral radius of the next-generation matrix and is obtained as Basic reproduction number ( ) is the crucial fact in analyzing the kinetics of the epidemic system ( 11 ).…”
Section: Consideration Of Subsystemmentioning
confidence: 99%
“…In this study, it is observed that the peak of infection (maximum of daily cases) is accomplished about 10 days after the commencement of confined process and the authors suggested to implement stricter measures as radically obligatory methods. Mondal et al [ 14 ] presented a seven compartmental SEIQR type model to explore the COVID-19 disease progression and the effect of pharmaceutical and non-pharmaceutical interventions as control input and there effects in reducing the number of the infected population.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the authors studied the coronavirus dynamics in the sense of fractional-order derivatives ([18, 19, 20, 21]). In cells level, the authors in [22] studied the dynamics of a fractional-order delay differential model for coronavirus (CoV) infection to give us best understand what causes the intensity of symptoms and illness of contaminated lung and respiratory system; See also [23, 24, 25].…”
Section: Introductionmentioning
confidence: 99%